2008
DOI: 10.1104/pp.108.118026
|View full text |Cite
|
Sign up to set email alerts
|

RUPTURED POLLEN GRAIN1, a Member of the MtN3/saliva Gene Family, Is Crucial for Exine Pattern Formation and Cell Integrity of Microspores in Arabidopsis      

Abstract: During microsporogenesis, the microsporocyte (or microspore) plasma membrane plays multiple roles in pollen wall development, including callose secretion, primexine deposition, and exine pattern determination. However, plasma membrane proteins that participate in these processes are still not well known. Here, we report that a new gene, RUPTURED POLLEN GRAIN1 (RPG1), encodes a plasma membrane protein and is required for exine pattern formation of microspores in Arabidopsis (Arabidopsis thaliana). The rpg1 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
232
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(261 citation statements)
references
References 43 publications
(66 reference statements)
8
232
0
1
Order By: Relevance
“…Some SWEETs showed higher expression levels in reproductive tissues especially in floral organs, such as SWEET1a_At/Dt (petals, sepals, and 10-25 DPA fibers), SWEET1b_At/Dt (stamen, − 1 DPA ovule, 1DPA and 5DPA seeds, 10 DPA fiber), SWEET2a_At/Dt (petals and stamens), SWEET7a_At/Dt (petals and stamens). The results indicated that SWEETs also involved in the reproductive development of cotton, consistent with the results in Arabidopsis and rice (Yuan et al 2009;Yuan et al 2010;Guan et al 2008;Sun et al 2013;Liu et al 2011;Ge et al 2000). In addition, SWEET2a_At/Dt, SWEET1b_Dt and SWEET4_At were detected with high expression levels in germinating seed, cotyledons and roots during germination (Fig.…”
Section: Expression Patterns Of Sweet Genes In Different Tissuessupporting
confidence: 77%
See 1 more Smart Citation
“…Some SWEETs showed higher expression levels in reproductive tissues especially in floral organs, such as SWEET1a_At/Dt (petals, sepals, and 10-25 DPA fibers), SWEET1b_At/Dt (stamen, − 1 DPA ovule, 1DPA and 5DPA seeds, 10 DPA fiber), SWEET2a_At/Dt (petals and stamens), SWEET7a_At/Dt (petals and stamens). The results indicated that SWEETs also involved in the reproductive development of cotton, consistent with the results in Arabidopsis and rice (Yuan et al 2009;Yuan et al 2010;Guan et al 2008;Sun et al 2013;Liu et al 2011;Ge et al 2000). In addition, SWEET2a_At/Dt, SWEET1b_Dt and SWEET4_At were detected with high expression levels in germinating seed, cotyledons and roots during germination (Fig.…”
Section: Expression Patterns Of Sweet Genes In Different Tissuessupporting
confidence: 77%
“…AtSWEET9 transports sucrose into apoplasts for nectar secretion (Lin et al 2014). AtSWEET8, a glucose transporter expressed in tapetum and embryo sacs, participates in the development of the pollen and anther (Guan et al 2008;Sun et al 2013). The silenced AtSWEET11 mutant showed lower pollen viability and even pollen sterility (Sonnewald 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen grains were then viewed with an Olympus BH-2 light microscope (Olympus Co., Ltd). SEM analysis was performed as described previously (47), and the samples were observed by a JSM-6360LV SEM (JEOL Ltd). For TEM analysis, the buds approximately containing stage-8 anthers were fixed and dehydrated as described by Zhang et al (48), imbedded in a mixture of Spurr's Resin to acetone with a ratio of 1:1 for 2 h and Spurr's Resin alone for 2 h, and the material was polymerized in molds at 35°C for 16 h and then 60°C for 48 h. Ultrathin sections (90-100 nm thick) were observed with a JEM-2100 TEM (JEOL Ltd).…”
Section: Methodsmentioning
confidence: 99%
“…Significant progress in our understanding of exine formation processes has been made recently, thanks to genetic and molecular studies of Arabidopsis mutants exhibiting defects in exine structure and deposition (Aarts et al, 1997;PaxsonSowders et al, 2001;Ariizumi et al, 2003Ariizumi et al, , 2004Ito et al, 2007;Morant et al, 2007;Yang et al, 2007;Guan et al, 2008;Suzuki et al, 2008;de Azevedo Souza et al, 2009;Dobritsa et al, 2009a;Tang et al, 2009). Unfortunately, in most cases, annotations of the mutated Arabidopsis genes found to be responsible for pollen phenotypes are primarily based on sequence similarity, and the exact functions of the corresponding proteins in pollen development remain unknown.…”
Section: Introductionmentioning
confidence: 99%